Lightweight aluminum joint design: Enhancement of mechanical properties through novel inter-layer and powder additives in friction stir welding - Equbal Ahmed; Muhammed Muaz; Sajjad Arif; Ravi Kant; Syed Mohd Hamza; Md Kashif Alim; Musab Ahmad Khan; Jaber Abu Qudeiri; Sanan H. Khan (International Journal of Lightweight Materials and Manufacture)
Friction Stir Welding (FSW) is a solid-state joining technique that has garnered significant attention for its ability to weld aluminum alloys while mitigating common issues such as porosity and thermal defects inherent in fusion welding. This study systematically evaluates the impact of inter-layers and powder additives on the mechanical properties of aluminum FSW joints. Magnesium (Mg) ribbons and Lead–Tin (Sn–Pb) alloy ribbons were employed as inter-layers, while Boron Carbide (B4C), Titanium Dioxide (TiO2), and Manganese (Mn) served as reinforcement powders. Quantitative analysis demonstrated that the combination of Manganese (Mn) powder and Sn–Pb alloy inter-layer achieved a remarkable 28 % improvement in hardness, a 35 % reduction in wear rate, and a 42 % increase in shear strength. Additionally, Mn powder alone yielded the highest shear strength, while Sn–Pb inter-layer with Mn powder provided maximum hardness and wear resistance. Mg ribbon combined with Mn powder produced the lowest surface roughness. These enhancements were corroborated by mechanical testing and morphological characterization, including scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and microstructural mapping. The findings highlight the effectiveness of tailored inter-layer and powder combinations in enhancing weld quality, providing insights into the underlying mechanisms responsible for these improvements. This study underscores the industrial relevance of these advancements, offering transformative potential for sectors such as aerospace and automotive manufacturing where superior joint properties are critical.